The Inverse Care Law programme: evaluating a population based intervention in primary care within deprived communities in Wales. (2018) - Song, Jiao; Akbari, Ashley; Cox, Caryn; May, Leon; Watkins, William; Aitken, Sarah; Thomas, Sarah; King, William
No abstract available